Performance of Teak (Tectona grandis Linn. F.) Clones of Andhra Pradesh - Rao, P. S.; Murali, V.; Venkaiah, K.; Murti, S. S. N. (Indian Forester, 2002)
Performance of teak bud wood grafts taken from 27 plus trees, representing different Forest Divisions of Andhra Pradesh State were evaluated for stand volume (m3/ha), PAI and MAI (m3/ha/year). The best performing clones (where MAI is more than 8 m3/ha/year) are APNBV-I, APNPMP-2, APSBC-l, APNDG-l and APNPMP-l. Physical characteristics of best performers are described in detail.